Characterising Biomarkers of Chronic Lung Disease in Survivors of Preterm Birth - Urs, Rhea Caroline (Curtin University, 2021)
This research found preterm-born children displayed poor respiratory outcomes, with evidence of increased neutrophilic inflammation and oxidative stress, rather than the eosinophilic profile associated with “typical” childhood asthma. Additionally, metabolomic analysis showed preterm-born individuals have an altered metabolome from those born at term. Together this research provides insight into the contributors of chronic lung disease providing opportunities for early intervention and better lifelong respiratory outcomes in survivors of preterm birth.